A novel UV-cured interpenetrating organic-inorganic hybrid polymer network based phase change materials (IPN-PCM) - KAHRAMAN, MEMET VEZİR (WILEY, 2018)
The purpose of this paper is to introduce a novel UV-cured interpenetrating polymer networked phase change materials (IPN-PCMs), on which no article has been found in the so far published research. Maleated castor oil (MCO) was synthesized via maleinization reaction of castor oil with maleic anhydride. Organic-inorganic hybrid interpenetrating polymer networked (IPN) materials containing both cationic and radical sections and IPN-PCMs containing tetradecanol, hexadecanol, and octadecanol were prepared. The chemical structure of MCO and organic-inorganic hybrid IPN-PCMs were determined by using Fourier Transform Infrared Spectroscopy (FT-IR). Differential scanning calorimetry (DSC) was used for examining the phase-change behaviors of the materials. Thermal stability was investigated by thermogravimetric analysis (TGA). Moreover, the surface formation of the specimen was investigated by scanning electron microscopy (SEM). In conclusion, our study proved that because of their high latent heat storage scope and high thermal stability, the obtained organic-inorganic hybrid IPN-PCMs could be used as thermal energy storage materials. POLYM. ENG. SCI., 58:870-875, 2018. (c) 2017 Society of Plastics Engineers
Keywords: STORAGE